Alternativna terapevtska skupnost Janeza Ruglja po modelu "velikih pet" - Bagon, Judita (Psihološka obzorja (Ljubljana), 2000)
The Alternative Therapeutic Community (ATC) of Dr. J. Rugelj is a specific social community consisting of people in distress (always consisting of about 120 people), who have all been handicapped in their lives in one way or another. The group is also specific because of their way towards recovery, i.e., intensively reactivating the mecanisms of healthy life to sermount theirpsychical and social deficiency. The results of measuring the structure of personality according to BFQ-the ĆBig FiveĆ model of personality-show that the ATC as a whole achieves lower scores than the normal population on all dimensions and subdimensions. The difference is statistically significant regarding the dimension of Emotional stability as well as the subdimension Emotional control. The ATC is not a uniform group, so the results differ according to the diagnosis. The members with the diagnosis of a neurotic or a psychotic achieve below-average results, while the accompanying members achieve similar results as the control group (selected from the non-members ofthe ATC). The results of the members diagnosed as Ćan alcoholicĆ are somewhat surprising-they do not differ considerably on any dimension or subdimension from the results achieved by the control group-not even on the Emotional stability scale. As regards the total period of staving in the program, the results of subdimensions remain mostly unchanged. However, duringthe time spent in the program the results on the subdimensions changeČ the group which has been in the program for 1 to 2 years generally scores higher than the group of beginners (the difference is statistically significant only for the dimension Emotional control), but the results of the group participating in the program for longer time (more than three years) arelower again, until they stabilize in the central position (T=50). (Abstracttruncated at 2000 characters).
Keywords: Rugelj, Janez, 1929-; terapevtske skupnosti; alkoholizem; therapy; zdravljenje; model velikih pet; psihologija osebnosti